Antimicrobial function of yeast against pathogenic and spoilage microorganisms via either antagonism or encapsulation: A review. (June 2023) - Ma, Yue; Wu, Mengjie; Qin, Xiaojie; Dong, Qingli; Li, Zhuosi
Abstract: Contaminations of pathogenic and spoilage microbes on foods are threatening food safety and quality, highlighting the importance of developing antimicrobial agents. According to different working mechanisms, the antimicrobial activities of yeast-based agents were summarized from two aspects: antagonism and encapsulation. Antagonistic yeasts are usually applied as biocontrol agents for the preservation of fruits and vegetables via inactivating spoilage microbes, usually phytopathogens. This review systematically summarized various species of antagonistic yeasts, potential combinations to improve the antimicrobial efficiency, and the antagonistic mechanisms. The wide applications of the antagonistic yeasts are significantly limited by undesirable antimicrobial efficiency, poor environmental resistance, and a narrow antimicrobial spectrum. Another strategy for achieving effective antimicrobial activity is to encapsulate various chemical antimicrobial agents into a yeast-based carrier that has been previously inactivated. This is accomplished by immersing the dead yeast cells with porous structure in an antimicrobial suspension and applying high vacuum pressure to allow the agents to diffuse inside the yeast cells. Typical antimicrobial agents encapsulated in the yeast carriers have been reviewed, including chlorine-based biocides, antimicrobial essential oils, and photosensitizers. Benefiting from the existence of the inactive yeast carrier, the antimicrobial efficiencies and functional durability of the encapsulated antimicrobial agents, such as chlorine-based agents, essential oils, and photosensitizers, are significantly improved compared with the unencapsulated ones. Highlights: In vivo and in vitro methods for screening antagonistic yeasts from fruits, vegetables, soils, and marines. Enhancing antimicrobial effect via combining other antagonistic microbes, physical treatments, and chemical agents. Four antagonistic mechanisms: competition, parasitism effect, production of antimicrobial agents, and host resistance. Embedding inactive yeast-based carriers with antimicrobial function via encapsulating antimicrobial chemicals.